Studi Kelimpahan Dan Keanekaragaman Kepiting Di Hutan Mangrove Dan Padang Lamun Di Pantai Mertasari - Indraswari, I Gusti Ayu Dian; Dirgayusa, I Gusti Ngurah Putra; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.162-170, 2017)
The ecosystem of mangroves and seagrass in Mertasari Beach are located nearby and and inhabited with various species that coexist, One of the association’s creature in mangrove ecosystem and seagrass ecosystem is crab. There were a habitat selection of crabs, so it does possible to find the same species in the mangrove ecosystem and seagrass ecosystem. This research aims to know the type, abundance and diversity of crabs in the Mertasari Beach on two different ecosystems such as mangrove and seagrass ecosystem. The research were conducted in January until February 2017. In this research the Random sampling method was used to create a 1x1m2 square placed on 5 substations at each research station. Crab sampling was conducted at the lowest tide and has been done twice in a month. The results showed there were 7 families with 20 species. In both ecosystem were found 3 spesies such as Scylla serrata, Grapsus albolineatus and Myomenippe fornasinii. This happens because of several factors, like the tidal and the flow of the river into habitat removal by crabs. The highest abundance of crabs was found in mangrove stations of 411 individuals/m 2 , while at the seagrass station were 93 individuals/m 2 due to food availability and environmental conditions. The highest value diversity index (H) at mangrove station was 1.94 and seagrass station of 1.73 with moderate category indicated in those area had sufficient productivity, conditions of the ecosystem is pretty balanced and moderate ecological pressure.